Partisan Publics : Communication and Contention across Brazilian Youth Activist Networks - Mische, Ann (Book collections on Project MUSE., 2008)
During the 1980s and 1990s, Brazil struggled to rebuild its democracy after twenty years of military dictatorship, experiencing financial crises, corruption scandals, political protest, and intense electoral contention. In the midst of this turmoil, Ann Mische argues in this remarkable book, youth activists of various stripes played a vital and unrecognized role, contributing new forms of political talk and action to Brazil's emerging democracy. Drawing upon extensive and rich ethnography as well as formal network analysis, Mische tracks the lives of young activists through intersect.